Hystero-laparoscopic communication of right non-communicating horn of Robert’s uterus in a 16-year-old girl with severe dysmenorrhea and hematometra: A case report - Abhinibesh Chatterjee; Polly Chatterjee; Avishek Bhadra; Rumela Biswas (Asian Journal of Medical Sciences, 2025)
Robert’s uterus, first described in 1970, is a rare variant of a complete, oblique septate uterus characterized by a non-communicating hemi-cavity and a contralateral unicornuate cavity. This anomaly can lead to obstructed menstrual flow, resulting in hematometra and associated complications such as hematosalpinx and endometriosis. We report a case of Robert’s uterus in a 16-year old girl presenting with severe dysmenorrhea and prolonged menstrual flow since menarche, highlighting the restoration of uterine anatomy. Previous magnetic resonance imaging indicated a Mullerian duct anomaly with a non-communicating rudimentary horn. After initial management involving hystero-laparoscopy and drainage of hematometra, she experienced recurrent dysmenorrhea. A second hystero-laparoscopic procedure revealed adhesions, and the non- communicating horn was surgically communicated with the main cavity. The patient was discharged with oral contraceptives, and follow-up ultrasound showed a normal sized uterus and regular, pain-free menstruation. Robert’s uterus arises from incomplete resorption of the uterine septum, leading to unique anatomical features and potential complications, including subfertility. Traditional management has included laparotomy; however, minimally invasive techniques such as hysteroscopy and laparoscopy are now preferred due to reduced surgical trauma and better preservation of fertility.